2012
DOI: 10.1103/physrevb.85.094510
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-surface topology and low-lying electronic structure of the iron-based superconductor Ca10(Pt3As8)(Fe

Abstract: We report a first study of low energy electronic structure and Fermi surface topology for the recently discovered iron-based superconductor Ca10(Pt3As8)(Fe2As2)5 (the 10-3-8 phase, with Tc ∼ 8 K), via angle resolved photoemission spectroscopy (ARPES). Despite its triclinic crystal structure, ARPES results reveal a fourfold symmetric band structure with the absence of Dirac-cone-like Fermi dots (related to magnetism) found around the Brillouin zone corners in other iron-based superconductors. Considering that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 41 publications
(55 reference statements)
6
47
0
Order By: Relevance
“…However, such hybridization between the Pt 5d and Fe 3d orbitals at E F is not clearly observed by angle-resolved photoemission spectroscopy (ARPES), indicating that the Pt 4 As 8 spacer layer is semiconducting. [7,8] On the other hand, another recent ARPES study has shown that the Pt 5d states have small contribution to the Fermi surfaces, partly consistent with the theoretical prediction. [9] In case of Ca 10 (Pt 4 As 8 )(Fe 2−x Pt x As 2 ) 5 , the contribution of the Pt 5d states at E F is rather small even though it may exist as predicted by the theory.…”
supporting
confidence: 72%
“…However, such hybridization between the Pt 5d and Fe 3d orbitals at E F is not clearly observed by angle-resolved photoemission spectroscopy (ARPES), indicating that the Pt 4 As 8 spacer layer is semiconducting. [7,8] On the other hand, another recent ARPES study has shown that the Pt 5d states have small contribution to the Fermi surfaces, partly consistent with the theoretical prediction. [9] In case of Ca 10 (Pt 4 As 8 )(Fe 2−x Pt x As 2 ) 5 , the contribution of the Pt 5d states at E F is rather small even though it may exist as predicted by the theory.…”
supporting
confidence: 72%
“…According to a former suggestion, such differences arise from the difference in the metallicity of the Pt n As 8 layers 14 , with the latter suggestion that the differences can develop from the number of band-edge singularities 15 . To investigate the effect of such subtle differences on the electronic structure and superconductivity, various experimental studies based on transport 11 , pressure effects 16 , NMR 17 , ARPES 18 , neutron 19 , and IR spectroscopy 12 have been carried out; thus, much progress has been made. However, detailed studies on the characteristic changes of superconducting gaps due to such differences in the electronic structure have rarely been carried out, with the in-depth understanding of the superconductivity mechanism, as well as the systematic development of superconductivity, having hardly progressed.…”
Section: Introductionmentioning
confidence: 99%
“…2 we show photon energy dependent measurements performed to reveal band dispersion in the k z direction. Figures 2(a)-2(d) show EDMs measured at the zone center using photon energies 20, 30, 40, and 80 eV and corresponding k z values are given by 8.55 π/c, 10.11 π/c, 11.46 π/c, and 15.7 π/c (c = 10.46Å and the inner potential is taken as 9.5 eV), 12 respectively. In Fig.…”
mentioning
confidence: 99%